2006
DOI: 10.1002/cncr.21687
|View full text |Cite
|
Sign up to set email alerts
|

K‐ras mutations and N‐ras mutations in childhood acute leukemias with or without mixed‐lineage leukemia gene rearrangements

Abstract: Objective Juvenile localized scleroderma (LS) is a chronic inflammatory skin disorder associated with substantial morbidity and disability. Although a wide range of therapeutic strategies has been reported in the literature, a lack of agreement on treatment specifics and accepted methods for clinical assessment has made it difficult to compare approaches and identify optimal therapy. Our objective was to develop standardized treatment plans, clinical assessments, and response criteria for active, moderate to h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
83
3

Year Published

2007
2007
2016
2016

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 86 publications
(92 citation statements)
references
References 54 publications
6
83
3
Order By: Relevance
“…Although the constitutively active mutants of STAT5A, the relatively stronger mutant STAT5A1*6 and weaker mutant STAT5A#2, enabled Ba/F3 cells (Ba/F3 1*6 , Ba/F3 # ) to grow without IL-3 as reported earlier, 25,27,28 both failed to confer factor-independent growth on HF6 cells with limited elongation of survival time without IL-3 (Figures 3a and c). In contrast, the oncogenic NRAS mutant, NRAS G12V , which had been detected in a case of AML with MLL-SEPT6, 20 enabled HF6 cells (HF6 G12V ) to grow without IL-3, while it conferred no factor-independent growth on Ba/F3 with limited elongation of survival time without IL-3 (Figures 3b and c). In addition, Raf-1, a signal molecule downstream of Ras in Ras-MAPK cascades associated with malignant transformation, was tested with an activation-inducible system using DRaf-ER, consisting of the catalytic domain of human RAF-1 (DRaf) and the hormonebinding domain of the ER (Figure 3d), as described earlier.…”
Section: Activation Of Ras-mapk Cascade Enables Hf6 Cells To Grow Witmentioning
confidence: 97%
See 1 more Smart Citation
“…Although the constitutively active mutants of STAT5A, the relatively stronger mutant STAT5A1*6 and weaker mutant STAT5A#2, enabled Ba/F3 cells (Ba/F3 1*6 , Ba/F3 # ) to grow without IL-3 as reported earlier, 25,27,28 both failed to confer factor-independent growth on HF6 cells with limited elongation of survival time without IL-3 (Figures 3a and c). In contrast, the oncogenic NRAS mutant, NRAS G12V , which had been detected in a case of AML with MLL-SEPT6, 20 enabled HF6 cells (HF6 G12V ) to grow without IL-3, while it conferred no factor-independent growth on Ba/F3 with limited elongation of survival time without IL-3 (Figures 3b and c). In addition, Raf-1, a signal molecule downstream of Ras in Ras-MAPK cascades associated with malignant transformation, was tested with an activation-inducible system using DRaf-ER, consisting of the catalytic domain of human RAF-1 (DRaf) and the hormonebinding domain of the ER (Figure 3d), as described earlier.…”
Section: Activation Of Ras-mapk Cascade Enables Hf6 Cells To Grow Witmentioning
confidence: 97%
“…6 Recent studies revealed that genetic alterations, including FLT3, NRAS (neuroblastoma RAS viral (v-ras) oncogene homolog) and KRAS (v-Ki-ras2 Kirsten rat sarcoma viral oncogene homolog), are frequently accompanied by 11q23 translocation. 19,20 FLT3 is a receptor tyrosine kinase involved in leukemogenesis and normal hematopoiesis. 21 The mutations of FLT3 are mainly classified into length mutations such as internal tandem duplication (ITD) of the juxtamembrane domain, and point mutations within the activation loop of the second tyrosine kinase domain (TKD).…”
Section: Introductionmentioning
confidence: 99%
“…11,16 Amplicons were generated on a 2720 Thermal cycler (Applied Biosystems, Foster City, CA, USA), polymerase chain reaction (PCR) mixture and cycling conditions are described in the Online Supplementary Table S1. Primer sequences were adapted from previous publications 11,16 and modified by additional M13 tags (Online Supplementary Table S1). Sequence analysis of both sense and antisense strands was carried out using M13 primers, and the BigDye terminator v1.…”
Section: Detection Of Nras Kras and Braf Mutationsmentioning
confidence: 99%
“…For instance, Liang et al reported RAS mutations in 10 of 20 (50%) of the cases, while Mahgoub et al could not identify RAS mutations among 13 MLLrearranged ALL samples. 11,12 Besides, Tamai et al speculate that the short latency in their KRAS mutation-positive mouse model is likely due to an acceleration of leukemolymphomagenesis by a collaborative upregulation of HOXA9. 9 HOXA overexpression is often believed to be a hallmark of MLL-rearranged leukemia and has recently been proposed to be required for leukemia survival of MLLrearranged acute myeloid leukemia (AML) cells.…”
Section: Introductionmentioning
confidence: 99%
“…24 DNA PCR or RT-PCR followed by direct sequencing was performed to detect mutations at codons 12, 13 and 61 of the N-and K-Ras genes. 25 …”
Section: Detection Of Csf1r Mutationsmentioning
confidence: 99%